Learning English pronunciation: Articulating EFL students’ voices on problems and strategies - Sibakhul Milad Malik Hidayatulloh (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
In mastering English language skills, the learning process matters in determining the goals, including learning pronunciation. So far, research on pronunciation has emphasized pronunciation rather than the process. Thus, this study aimed to investigate students' problems and techniques for dealing with problems in acquiring pronunciation. Six English Department students were voluntarily requested to participate in this study and discuss their perspectives. In data collection process, an in-depth interview was employed. The findings found that participants had difficulties distinguishing between sounds and words, encountered novel words, had low learning desires, dealt with varied accents, and experienced interference from their language. In the other sense, they applied some strategies such as increasing exposure to English, having expert guidance, and pursuing to have a severe problem. The results of this study will play a positive role in showing the barriers experienced by students when learning pronunciation. Thus, it is hoped that the teachers will be aware of these issues, so that teaching pronunciation will be more effective.DOI: 10.26905/enjourme.v7i2.8496